ANALISIS MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MINAT BELAJAR SISWA MELALUI PEMBELAJARAN BERBASIS TEKNOLOGI - Nila Dwi Agustin; Alwahyuni Purnama Dewi; Moh Rifqi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the role of technology-based learning media in increasing students interest in learning through a literature review of various related journals. With the development of technology, the use of technology-based learning media is believed to provide a more interesting and effective learning experience. The method used in this study is a qualitative research method with data collection techniques in the form of literature studies, which include analysis of relevant scientific journals. The results of the study indicate that technology-based learning media, such as learning applications, educational videos, and other digital playforms, have great potential in increasing student interest in learning by creating an interactive, flexible, and easily accessible learning environtment.